Derivation of this
v=u+at
Answers
So we have to derive …
v = u + at ….
Which is First equation of motion ….
So , to derive it I am going to use Integration method ….
In the equation v = u+ at ….
v = final velocity
u = initial velocity
a = acceleration
t = time period of acceleration
Here we should note that acceleration is constant ….
So let's start to derive First equation of motion ..
We know that
a = dv/dt
So …
dv = adt
Now integrating both sides ….
So I cannot find some of the mathematical symbols in my phone's keyboard so I cannot write the answer but I will provide a pic of derivation of First equation of motion using integration …
I hope you that the given answer is helpful to everyone …
If there is any mistake in my way of derivation then please tell in the comment section below .
Thank you very much for reading my answer and don't forget to upvote if the answer is useful to you .
4.1k Views ·
How anonymous is DuckDuckGo?
Before getting to the derivation. Note that, acceleration (a) is nothing but rate of change of velocity. Framing up this sentence as a equation we get
acceleration (a) = rate of change in velocity (or) change in velocity per unit time = change in velocity/time …………………………………..eq(1)
Let us assume the initial velocity to be ‘u' and final velocity be ‘v' and the taken to attain the final velocity from the initial be ‘t'
Therefore, change in velocity = v-u
Now equation (1) becomes,
→a=(v-u )/t
→at=v-u
And therefore, v=u+at
14.9k Views ·
Your feedback is private.
Is this answer still relevant and up to date?
Originally Answered: What is the derivation of the formula v=u+at?
Let the velocity of an object increase from u m/s to v m/s in time t
Then the rate of change of velocity with respect to time is given by
(v - u)/t. This quantity is called acceleration and given the symbol a
That is (v - u)/t = a
v - u = at ………..multiplying both sides by t
v = u + at ………….adding u to both sides
Hey mate,
V=u+at.
Here, V= final velocity.
U=initial velocity.
a=acceleration.
t=time taken.
Now, as we know:
a/1 =(v-u)/t.
CROSS MULTIPLING,we get:
v-u=at.
which is equal to v=u+at.
HOPE IT HELPS!
plss mark me as brainliest!